2015
DOI: 10.1016/j.pec.2014.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing intercultural doctor–patient communication: A realist review

Abstract: Training for improving ICC can be developed as an extension of the existing training for patient-centered communication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
94
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 122 publications
(108 citation statements)
references
References 146 publications
(156 reference statements)
7
94
1
1
Order By: Relevance
“…Mental wellbeing may be particularly relevant in consultations to reach a PCP agreement (Paternotte et al 2015). Studies suggest ethnic inequalities in doctor patient interactions (Burt et al 2016, Volz, Moore, and Belkora 2015, Ahmed et al 2015, Croker et al 2013, Wong et al 2014, Murray Garcia et al 2000, Lyratzopoulos et al 2012).…”
Section: ! "mentioning
confidence: 99%
See 4 more Smart Citations
“…Mental wellbeing may be particularly relevant in consultations to reach a PCP agreement (Paternotte et al 2015). Studies suggest ethnic inequalities in doctor patient interactions (Burt et al 2016, Volz, Moore, and Belkora 2015, Ahmed et al 2015, Croker et al 2013, Wong et al 2014, Murray Garcia et al 2000, Lyratzopoulos et al 2012).…”
Section: ! "mentioning
confidence: 99%
“…In the UK people of South Asian descent generally report poorer doctor patient experiences compared with Caucasians (Ahmed et al 2015, Burt et al 2016). A recent systematic review of the literature in this area identified negative psychological factors (e.g., perceived prejudice) affecting intercultural doctor patient interactions (Paternotte et al 2015). While evidence suggests positive mental wellbeing can help improve the patients' experience (Folkman 1997, Edwards and Cooper 1988, Salovey et al 2000, Fredrickson 1998, it is unclear to how this applies to PCP consultations, particularly in an intercultural context (Paternotte et al 2015).…”
Section: ! "mentioning
confidence: 99%
See 3 more Smart Citations